Fame, but no riches, for cybersecurity. - Farber, D. (IEEE spectrum)
The road to a secure computer infrastructure still has lots of potholes. Perhaps the deepest and widest is the attitude of senior management in government and industry toward cybersecurity. Often they say the right words as they scale back the research support and manpower needed to study the issues involved and start to fix it. Financial institutions, which are among our most vulnerable, lay off people with security backgrounds. Computer professionals with excellent skills are walking the streets with no job prospects. There is a striking disconnect between the problems these institutions face and their willingness to make an investment in protecting themselves. Meanwhile, the clock is ticking. The time for report-writing is past.